An Analysis of Thai Public Administration: From Past to Present - sarakarn, alongkot (King Prajadhipok’s Institute Journal, 2020)
The purposes of this academic article were to, firstly, review important paradigms of public administration, and secondly, review the development of Thailand’s public administration system. The study identified four important paradigms of public administration: (1) traditional public administration, (2) new public management (3) new public service and (4) new public governance paradigm. Review of the development of Thailand’s public administration system revealed five bureaucratic reform periods and explored the reasons that prompted each reform. The five periods are: (1) reform of the Thai bureaucracy during the reign of King Rama III (1448 - 1470); (2) reform of the Thai bureaucracy during the reign of King Chulalongkorn (1868 - 1910); (3) reform of the Thai bureaucracy in 1933; (4) reform of the Thai bureaucracy in 2002; and (5) guidelines for the reform of the Thai bureaucratic system according to the Constitution of the Kingdom of Thailand 2017.